أخطاء المعالجة الإحصائية في بحوث علم النفس وعلوم التربية - جعفور, ربيعة (جامعة الوادي University of Eloued, 2017)
يهدف هذا المقال إلى رصد بعض أخطاء المعالجة الإحصائية الشائعة في بحوث علم النفس وعوم التربية وممارسات بعض الباحثين- المبتدئين خاصة – وتبعا للتراث النظري ونتائج الدراسات السابقة حول ذات الموضوع أمكن تصنيفها إلى ثلاث فئات من حيث( المفاهيم، التدريس، الممارسات) وخلصت عملية التحليل إلى ضرورة تحلي الباحث بمهارة التحليل الإحصائي والأخلاقيات الإحصائية ضمانا لصدق النتائج. This article aims at monitoring some of the Common statistical processing errors in the research of psychology and éducation and the practices of some researchers - beginners especially - and according to the theoretical heritage and the results of previous studies on the same subject can be classified into three categories in terms of (concepts, teaching, The researcher must be skilled in statistical analysis and statistical ethics in order to guarantee the accuracy of the results.
مقال
Keywords: المعالجة الإحصائية؛ الصدق الإحصائي؛ الأخلاقيات الإحصائية; Statistical processing, statistical honesty, statistical Ethics